Antiangiogenic Tetrathiomolybdate Protects Against Her2/neu-induced Breast Carcinoma by Hypoplastic Remodeling of the Mammary Gland - Pan, Quintin (2009)
PURPOSE: The development of cancer chemopreventative agents with increased safety profile is a major priority of cancer research. The objective of the present study was to delineate the efficacy of tetrathiomolybdate (TM), a novel antiangiogenic anticancer agent, as a chemopreventative agent. EXPERIMENTAL DESIGN: Nulliparous Her2/neu transgenic mice were treated with water or TM for 180 days and observed for tumor development during treatment and for 180 days post-treatment. Mammary gland composition and architecture were also observed following TM treatment of Her2/neu transgenic and normal FVB mice. RESULTS: At the 1-year follow-up, 86.7% of control and 40% of TM-treated Her2/neu mice had palpable mammary tumors with a median time to tumor development of 234 days (202, 279; 95% confidence interval) for control and greater than 460 days for TM-treated mice (p<0.0005, n=15). The mammary glands from TM-treated Her2/neu and FVB mice showed a blunted epithelial ductal branching system due to a significant decrease in the number of secondary branches and total number of differentiated mammary epithelial cells. Microvessel density in Her2/neu and FVB mammary glands was lowered by 65.6 ± 6.2% and 50.9 ± 4.5% (p<0.005) following TM therapy, consistent with the antiangiogenic effect of TM. Lastly, TM treatment resulted in a 2-fold increase in the absolute number of ALDH+ mammary stem cells in Her2/neu and FVB mammary glands. CONCLUSION: Taken together, these results strongly support that TM is a potent chemopreventative agent as a consequence of hypoplastic remodeling of the mammary gland through modulation of the mammary stem cell compartment.